2014
DOI: 10.1186/s13028-014-0063-1
|View full text |Cite
|
Sign up to set email alerts
|

A dose-finding, long-term study on the use of calcium chloride in saline solution as a method of nonsurgical sterilization in dogs: evaluation of the most effective concentration with the lowest risk

Abstract: BackgroundCanine overpopulation is a global issue with serious health and welfare implications. Nonsurgical methods of sterilization could yield positive impacts on this problem, but no long-term data on such methods are available. The objective of the current investigation was to determine the effects of intratesticular injections of calcium chloride dihydrate (CaCl2) in saline in dogs over a one year period. Five concentrations (0%, 10%, 20%, 30%, 60%) of CaCl2 in saline were administered via intratesticular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
30
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 18 publications
11
30
0
Order By: Relevance
“…In the present study, the different doses of the different chemo-sterilizing agents injected by intra-testicular route were determined to have caused severe oligozoospermia and azoospermia. The maximum response for the spermatological parameters was achieved in Group V. Similar to the results of the present study, Leoci (2014) reported that in dogs administered with 10 and 20 mg CaCl 2 asthenozoospermia and oligozoospermia was detected. Furthermore, in several studies carried out in rams, male rats, bucks and male dogs, it has been reported that the intra-epididymal injection of CaCl 2 reduces the concentration of spermatozoa (Jana et al 2002, Okwee-Acai et al 2008.…”
Section: Discussionsupporting
confidence: 80%
“…In the present study, the different doses of the different chemo-sterilizing agents injected by intra-testicular route were determined to have caused severe oligozoospermia and azoospermia. The maximum response for the spermatological parameters was achieved in Group V. Similar to the results of the present study, Leoci (2014) reported that in dogs administered with 10 and 20 mg CaCl 2 asthenozoospermia and oligozoospermia was detected. Furthermore, in several studies carried out in rams, male rats, bucks and male dogs, it has been reported that the intra-epididymal injection of CaCl 2 reduces the concentration of spermatozoa (Jana et al 2002, Okwee-Acai et al 2008.…”
Section: Discussionsupporting
confidence: 80%
“…Chemical sterilization with CaCl 2 in dogs (Jana & Samanta, ; Leoci, Aiudi, Silvestre, Lissner, & Lacalandra, ; Leoci, Aiudi, Silvestre, Lissner, Marino, et al, ; Mitra & Samanta, ) did not use the combination with DMSO. Thus, in our knowledge, this is the first description of this association.…”
Section: Discussionmentioning
confidence: 99%
“…In dogs, the effects of CaCl 2 injected intratesticularly have been investigated at concentrations of 5, 7.5, 10, 12.5, 15, 20, 30 and 60 mg/kg (Jana & Samanta, 2007;Leoci, Aiudi, Silvestre, Lissner, Marino, et al, 2014;Samanta, 1998). In those studies, the dogs did not show changes in physiological parameters and food consumption throughout the trial period, except for testicular swelling at 24 hr after the injection.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical castration using a solution of calcium chloride (CaCl 2 ) in dogs with high concentrations (10-20%) was reported not effective, where the testis still produced sperm (Leoci et al, 2014). On their study, the effectiveness of CaCl 2 solution for chemical castration were shown at a concentration of 30% after one year of observation.…”
Section: Jurnalmentioning
confidence: 98%